Evaluation of internal and external hexagon connections in immediately loaded full‐arch rehabilitations: A within‐person randomized split‐mouth controlled trial with a 3‐year follow‐up. (4th July 2021) - Pera, Francesco; Menini, Maria; Bagnasco, Francesco; Mussano, Federico; Ambrogio, Giulia; Pesce, Paolo
Abstract: Background: Although full‐arch immediately loaded rehabilitations are widely used nowadays, little information is available on which implant/abutment connection is the most suitable in this type of treatment. Purpose: The aim of the present multicentric split‐mouth clinical trial was to compare the clinical outcomes of two different implant‐abutment connections applied in full‐arch immediate loading rehabilitations: external hexagon connection (EHC) versus internal hexagon connection (IHC). Materials and methods: Twenty patients were rehabilitated with immediately loaded fixed full‐arch rehabilitations. All the implants presented the same macro‐ and micro‐topography but different implant/abutment connection. IHC were used in one randomly selected side of the jaw and EHC in the other side. Outcome measures were implant survival rate, peri‐implant marginal bone loss (MBL), plaque index (PI), probing depth (PD), and bleeding on probing (BoP) evaluated at 3, 6, 12, and 36‐month post‐loading. Any technical and biological complication was recorded. Kaplan–Meier procedure and linear mixed model were used to perform statistical analysis. Results: Forty‐three EHC and 40 IHC implants were inserted. No patients dropped out and two implants failed in the first 6 months. The CSR was 97.7% for EHC and 97.5% for IHC implants. No statistically significant differences were found among the two groups for any of the parameters at any time point. At the 36‐month follow‐up visit a slight difference was found in MBL with a mean value of 1.7 mm in the EHC and of 1.9 mm in the IHC group ( p = 0.355). No biologic complications were identified. Seven loosed abutment screws were identified in the entire follow‐up period, two in the EHC, and five in the IHC group without a statistically significant difference ( p = 0.394). Conclusions: After 36 months in function, both internal and external hexagon connections provided good clinical outcomes and were not associated with any significant difference.